DAMPAK PENGARUH PELATIHAN DAN PENGEMBANGAN TERHADAP KINERJA KARYAWAN DI PT PEGADAIAN CABANG MEDAN SUNGGAL YANG DIMEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Ambarita, Margaretha; Ario, Firman; Yanti, Eli Delvi (UNIKA Santo Thomas, 2025)
This study aims to examine the influence of training, development, employee performance, and organizational citizenship behavior (OCB) at PT Pegadaian Medan Sunggal Branch. A quantitative approach was used, with data analysis conducted through Smart PLS version 4.0. The research involved the entire population of employees, totaling 36 individuals, using a census sampling method. The results indicate that both training and development do not have a significant effect on OCB. However, training shows a significant impact on employee performance, while development does not. Additionally, OCB was found to have no significant effect on employee performance. Furthermore, the indirect effects of training and development on performance through OCB were also found to be insignificant. These findings suggest that while training may contribute to improved employee performance, OCB does not serve as a strong mediating variable in this organizational context. Therefore, a more integrated human resource development strategy is necessary to optimize both performance outcomes and positive employee behavior in the workplace.